Tryptophan-Mediated Interactions between Tristetraprolin and the CNOT9 Subunit Are Required for CCR4-NOT Deadenylase Complex Recruitment. Issue 5 (2nd March 2018) - Bulbrook, D.; Brazier, H.; Mahajan, P.; Kliszczak, M.; Fedorov, O.; Marchese, F.P.; Aubareda, A.; Chalk, R.; Picaud, S.; Strain-Damerell, C.; Filippakopoulos, P.; Gileadi, O.; et al.
Abstract: The zinc-finger protein tristetraprolin (TTP) binds to AU-rich elements present in the 3′ untranslated regions of transcripts that mainly encode proteins of the inflammatory response. TTP-bound mRNAs are targeted for destruction via recruitment of the eight-subunit deadenylase complex "carbon catabolite repressor protein 4 (CCR4)-negative on TATA-less (NOT), " which catalyzes the removal of mRNA poly-(A) tails, the first obligatory step in mRNA decay. Here we show that a novel interaction between TTP and the CCR4-NOT subunit, CNOT9, is required for recruitment of the deadenylase complex. In addition to CNOT1, CNOT9 is now included in the identified CCR4-NOT subunits shown to interact with TTP. We find that both the N- and C-terminal domains of TTP are involved in an interaction with CNOT9. Through a combination of SPOT peptide array, site-directed mutagenesis, and bio-layer interferometry, we identified several conserved tryptophan residues in TTP that serve as major sites of interaction with two tryptophan-binding pockets of CNOT9, previously found to interact with another modulator GW182. We further demonstrate that these interactions are also required for recruitment of the CCR4-NOT complex and TTP-directed decay of an mRNA containing an AU-rich element in its 3′-untranslated region. Together the results reveal new molecular details for the TTP-CNOT interaction that shape an emerging mechanism whereby TTP targets inflammatory mRNAs for deadenylation and decay. Graphical Abstract: Image 1 Highlights: TTP targets inflammatory mRNA for degradation by interacting with CCR4-CNOT complex. We identified one subunit of the complex, CNOT9, as a novel interactor of TTP. TTP binds using conserved Trp residues to CNOT9 regions common to other modulators. Trp-mediated interactions with CNOT9 are essential to TTP-mediated decay.